UJI VALIDITAS DAN RELIABILITAS KUESIONER PERILAKU PROSOSIAL - Esi Rosita; Wahyu Hidayat; Wiwin Yuliani (IKIP Siliwangi, 2021)
Good prosocial behavior is important for students to support student success in both the social and academic fields. The one of the measuring tools that can be used is a questionnaire. The purpose of this research is to make a questionnaire along with the validity and reliability test of the questionnaire. The research used is a R&D method with 13 respondents of class XI at SMK Aloer Wargakusumah. Based on the results of the research, it is known that the questionnaire test with 50 statement items shows that there are 36 valid statement items with a comparison between rcount> rtable. While the reliability test shows the Cronbach Alpha value> 0.60, then the questionnaire can be said to be reliable or consistent with the moderate category according to Sugiyono's criteria table. Keywords: prosocial behavior, questionnaire, validity and reliability test